2013
DOI: 10.1093/brain/aws286
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of purinergic signalling improves recovery from traumatic brain injury

Abstract: The recent public awareness of the incidence and possible long-term consequences of traumatic brain injury only heightens the need to develop effective approaches for treating this neurological disease. In this report, we identify a new therapeutic target for traumatic brain injury by studying the role of astrocytes, rather than neurons, after neurotrauma. We use in vivo multiphoton imaging and show that mechanical forces during trauma trigger intercellular calcium waves throughout the astrocytes, and these wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 54 publications
4
69
1
Order By: Relevance
“…In vivo imaging studies on the exposed rat cortex revealed that a micromechanical impact triggered intercellular Ca 2+ waves in cortical astrocytes which were attenuated by addition of the ATP-degrading enzyme apyrase. The data suggested that mechanical trauma to astrocytes in vivo triggers ATP-mediated Ca 2+ waves transmitting even beyond the initial epicenter of mechanical trauma [98]. These studies imply that cultured astrocytes represent a reactive phenotype different from in situ Bresting^astrocytes.…”
Section: Atp-mediated Atp Releasementioning
confidence: 84%
See 1 more Smart Citation
“…In vivo imaging studies on the exposed rat cortex revealed that a micromechanical impact triggered intercellular Ca 2+ waves in cortical astrocytes which were attenuated by addition of the ATP-degrading enzyme apyrase. The data suggested that mechanical trauma to astrocytes in vivo triggers ATP-mediated Ca 2+ waves transmitting even beyond the initial epicenter of mechanical trauma [98]. These studies imply that cultured astrocytes represent a reactive phenotype different from in situ Bresting^astrocytes.…”
Section: Atp-mediated Atp Releasementioning
confidence: 84%
“…More recent studies suggest, however, that in vivo astrocytic calcium waves occur only following a pathological insult [356]. This includes brain ischemia [357] and traumatic brain injury [98]. In vivo imaging studies on the exposed rat cortex revealed that a micromechanical impact triggered intercellular Ca 2+ waves in cortical astrocytes which were attenuated by addition of the ATP-degrading enzyme apyrase.…”
Section: Atp-mediated Atp Releasementioning
confidence: 99%
“…We used the mixed model structure to evaluate the latency times over consecutive trials in the first half (trials 1-4) and second half (trials 5-8), consistent with previous work. 15 If the mixed model produced significant differences for the fixed effects measures and/or their interaction across these two trial groups, we then used the Tukey honest significant difference (HSD) testing for post hoc comparison.…”
Section: Statistics For Behavioral Testsmentioning
confidence: 99%
“…A study investigated the role of P2 receptor antagonists in TBI [93]. A controlled cortical impact was applied to the head of mice with a pneumatic impactor.…”
Section: Protective Effects Of P2y Receptors In Vivo In Animal Modelsmentioning
confidence: 99%
“…The mechanism of protection is unclear, but reduced release of glutamate may inhibit excitotoxicity. Blocking hippocampal P2Y 1 receptors might lead to an enhancement of synaptic signaling which might trigger pro-survival pathways and antioxidant mechanism [93].…”
Section: Protective Effects Of P2y Receptors In Vivo In Animal Modelsmentioning
confidence: 99%